Inhibitory Effects of 3-(4-Hydroxy-3-methoxyphenyl) Propionic Acid on Amyloid β-Peptide Aggregation In Vitro - Makoto Mori; Hiroto Nakano; Sadao Hikishima; Jota Minamikawa; Daiki Muramatsu; Yasuhiro Sakashita; Tokuhei Ikeda; Moeko Noguchi-Shinohara; Kenjiro Ono (Biomedicines)
Objectives: The compound 3-(4-Hydroxy-3-methoxyphenyl) propionic acid (HMPA) is a terminal metabolite derived from polyphenol compounds. It has been studied for its potential to support brain health indirectly through its anti-oxidant effects and ability to enhance the gut environment; however, its role in dementia pathogenesis is unclear. Therefore, the aim of this study was to evaluate how HMPA inhibits Aβ42 aggregation in vitro. Methods: We examined the inhibitory effects of HMPA on amyloid-β protein (Aβ) aggregation using a thioflavin T (ThT) assay and electron microscopy (EM). Results: ThT assays demonstrated that HMPA inhibited both the nucleation and elongation phases of Aβ aggregation. Additionally, EM of low-molecular-weight (LMW) Aβ42 in the presence of HMPA demonstrated shorter fibrils compared to those formed without HMPA. The EC50 of HMPA in LMW Aβ42 was 5–6 mM. Conclusions: These findings indicate that, similar to several polyphenol compounds such as myricetin and rosmarinic acid, HMPA may inhibit Aβ pathogenesis, although it requires a fairly high concentration in vitro. These findings suggest the potential of HMPA as a lead compound for modulating Aβ-related neurodegeneration.